Spoken discourse in the tertiary mathematics classroom - Nivera, Gladys C. (2003)
Until recently, it has been assumed that mathematics transcends language factors. This belief is so pervasive that many bilingual education policies have promoted mathematics as one subject that can be taught in the students' weaker or second language (Khisty, 1993). Such is the case in the Philippines. Mathematics teachers are observed to distance themselves from issues concerning language use in their classrooms in the belief that mathematics and language learning do not mesh. But communication in the classroom is largely facilitated through language, and meaning is mediated through communication.Thus, contrary to the popular notion that mathematics and language lie at the opposite ends of a spectrum, they are in fact complementary: Language is a major vehicle for content learning in the same manner that engaging in meaningful content is a vehicle for language learning.
Includes bibliographical references (pages 12-13).